POLA INFESTASI PARASIT ARTHROPOB PADA TIKUS DI KEBUN RAYA PURWODADI, JAWA TIMUR - SRI HARTINI (BERITA BIOLOGI, 1985)
SRI HARTINI. 1985. The infestation pattern of arthropod parasites on rat at Purwodadi Botanical Garden. East Java. Berita Biologi 3(3) : 108-110. An investigation to find out the pattern of infestation of arthropod parasites on Rattus tiomanicus and Rattus rattus diardi was conducted in Purwodadi Botanical Garden, East Java. The parasites studied were Laelaps nutalli, Echinolaelaps echidninus (Acarina), Hoplopleura pacifica, Polyplax spinulosa (Anoplura) and Xenopsylla cheopis (Siphonaptera). It was concluded that parasite prevalence depends on habitat, age and sex of the host.The number of parasite infesting R. tiomanicus is greater than that of R.r. diardi, Adult rats have a higher prevalence rate than juveniles; likewise female adult rats are also higher than other sex and age group.